Psychometric Analysis of the Coronavirus Anxiety Scale in Argentinean Population - Leandro Eidman; Julieta Arbizu; Agustín Marturet (Interacciones)
Background: The purpose of this research was to analyze the psychometric properties of the Coronavirus Anxiety Scale to measure anxiety symptoms associated with COVID-19 in a sample of the Argentine population. Method: A non-randomized sample of 1098 subjects residing in different provinces of the Argentine Republic was used. The average age was 36.68 (SD = 14.34, Min = 18, Max = 83), 78.1% were women and 21.9% were men. A non-experimental, cross-sectional, instrumental study was designed. The epistemological basis used was classical psychometry. Results: Psychometric analyses reported that the scale has a one-dimensional structure with adequate reliability and validity (Ω = .93). The items met expected values for their discrimination, which showed that the instrument can distinguish between people with presence or absence of anxiety symptoms associated with Sars-Cov-2. The cut-off point for symptomatic identification was ≥ 10. The prevalence of anxiety symptoms by coronavirus was 22.4%. Conclusions: It can be concluded that this scale has an adequate format for its use in the Argentinean population in the context of coronavirus pandemic and its basic psychometric analysis indicated a good general performance of its measures, which allows identifying the presence or absence of anxiety symptoms.